An Analysis of English Final Semester Test Items at SMK Kencana Sakti Haumeni - Sanam, Asrit Elusry; Beeh, Norci; Snae, Alfred (Journal of Language, Education, Literature, and Culture, 2025)
Abstract This study aims to analyze the quality of the English final semester test items developed by the English teacher of SMK Kencana Sakti Haumeni. The research focuses on evaluating the test’s effectiveness by examining the difficulty level and discrimination power of each item. Using a quantitative descriptive approach, the study analyzed 50 multiple-choice items from the English summative test administered to second-grade students. The data were obtained through documentation, including students’ answer sheets and the original test papers. The analysis employed Heaton’s (1988) formulas to determine the facility value and discrimination index, supported by classifications from Sumarsono and Arikunto (Hartati & Yogi, 2019). The results revealed that 18% of the items were difficult, 50% were moderate, and 32% were easy. In terms of discrimination power, 22% of the items were categorized as good, 30% satisfactory, 40% poor, and 8% bad or negative. These findings suggest that although most test items met acceptable quality standards, a considerable number of items still require revision or replacement to enhance their ability to distinguish between high and low achievers. This study highlights the importance of item analysis as a reflective tool for teachers to ensure that classroom assessments are valid, reliable, and aligned with learning objectives. Regular evaluation of test items is therefore essential to improve the overall quality of English language assessment in schools.